BIMBINGAN KELOMPOK DENGAN TEKNIK SELF-MANAGEMENT UNTUK MENGATASI KECEMASAN SISWA MTS TERHADAP KEGIATAN E-LEARNING. - Anisa Yuniarti; Siti Fatimah; Rima Irmayanti (IKIP Siliwangi, 2022)
The implementation of e-learning during the pandemic is a new breakthrough for the learning system in Indonesia, but this new thing is certainly a burden for students and teachers because it takes a long time to adapt. E-learning makes it easier for students to get material flexibly and be able to evaluate their own learning anywhere. However, behind this convenience, e-learning makes students misuse the learning system and learning time to play. This happens because students consider the tasks and materials given by the teacher to be unimportant, even the learning atmosphere is considered saturated. In the end, the negative impact formed an anxiety, especially for the students of MTs Darussalam to make their achievement decline. Self-management technique group guidance is an alternative solution for BK teachers to stimulate students' anxiety into positive energy. This research was conducted using descriptive qualitative method with research subjects from two sources, namely six students of Class 8B and one BK teacher. The results of this study prove that the self-management technique group guidance service carried out with the stages of self-awareness, self-evaluation and self-reinforcement, this service succeeded in reducing anxiety levels and helping students manage their anxiety. This is a new reference for BK MTs Darussalam teachers to provide similar services so that all students can minimize anxiety levels during e-learning. Keywords: : E-Learning, Anxiety, Teknik Self Management